EVALUATION OF OVERLAY PERFORMANCE WITH REFERENCE TO WEARING COURSE COMPOSITION - Fatah Nurdin, Abdul
The aggregate grading of the mix used in overlay construction has a significant influence on the pattern of deterioration subsequently observed. The frequent observation of cracking in continuously graded mix as used in overlays in Indonesia led to the specification of gap-graded aggregate for use in overlays constructed in IBRD VI. The work described in this thesis is concerned with an evaluation of the composition of wearing course mixes installed on selected road links and an attempted correlation of observed performance with mix characteristic through: to have a significant influence on performance. The sections analysed are located on the Cirebon-Losari and the Ciawi-Cianjur links. Of the 50 samples of overlay wearing course taken on these \'links none met the Bina Marga aggregate grading specification for High-Durability Asphalt and only 2 mixes, on the Cirebon-Losari link, were within the range specified in BS-594 for British gap-grading wearing course mix. The Bina Marga Laston specification (Asphalt Concrete) was met by 9 out of 20 samples taken on the Cirebon-Losari link and 24 out of 30 samples taken on the Ciawi-Cianjur link. A total of 16 samples failed to meet any of these three specifications. Correlations between a range of wearing course characteristics and total rut depth of the overlaid pavement were very poor. Analysis of the composition of mixes that gave apparently satisfactory performance in situ permitted limits to be put on parameters considered critical to good performance. Laboratory tests were made on mixes prepared to the limits and median of those parameters, together with the corresponding IBRD mixes. In general these mixes failed to comply with specified Marshall tability and air voids content criteria. Ranking of performance according to Marshall criteria was not consistent with that indicated by the wheel-tracking test parameters.